2017
DOI: 10.1371/journal.pone.0181567
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone prescribing and initial BMI SDS: Increased biochemical adverse effects and costs in obese children without additional gain in height

Abstract: BackgroundRecombinant human growth hormone (rhGH) treatment in children is usually prescribed using actual body weight. This may result in inappropriately high doses in obese children.MethodsRetrospective audit of all paediatric patients treated with rhGH 2010–14 at a tertiary paediatric hospital in the UK. Change in height SDS and IGF-I SDS during the first year of treatment was stratified by initial BMI SDS in a mixed cohort, and a subgroup of GH deficient (GHD) patients. Alternative doses for those BMI SDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…However, data on serum IGF-I level in obese individuals are controversial, with studies reporting low 2124 , high 2527 , and normal levels 28,29 . Moreover, some studies have reported no relationship between IGF-1 and BMI SDS, and increased IGF-1 in obese GHD which supports our results 30 . This suggests that a modified GH-IGF-1 axis in obese children can only be meaningfully interpreted by measuring free IGF-1 to determine the true effects of BMI considering various factors 3133 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, data on serum IGF-I level in obese individuals are controversial, with studies reporting low 2124 , high 2527 , and normal levels 28,29 . Moreover, some studies have reported no relationship between IGF-1 and BMI SDS, and increased IGF-1 in obese GHD which supports our results 30 . This suggests that a modified GH-IGF-1 axis in obese children can only be meaningfully interpreted by measuring free IGF-1 to determine the true effects of BMI considering various factors 3133 .…”
Section: Discussionsupporting
confidence: 92%
“…There have been few studies on the impact of BMI on GHT in children with GHD; the studies showed an inverse relationship between BMI and first-year growth response 34 , or vice versa 30 . Hawcutt et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to the BMI reference norm for Chinese children and adolescences, subjects were considered to be obese when the BMI exceeded 95th percentile of the norm [ 17 ]. BMI standard deviation score (SDS-BMI) were calculated according to WHO BMI-for-age (5–19 years) [ 18 ].Subjects were diagnosed with hypertriglyceridemia (serum TG level > 1.7 mmol/L) according to the new International Diabetes Federation definition for Chinese people [ 19 ]. The study protocol was approved by the Ethical Committee of Xi’an Jiaotong University.…”
Section: Methodsmentioning
confidence: 99%
“…With the inclusion of pediatric subjects as a standard part of clinical development, more data are being collected so that drug development in children has expanded far beyond simple description of a small group of heterogeneous subjects. Beyond studying children of all ages, the problem of the correct dose for obese or underweight children is beginning to get attention. Perhaps more importantly, the advances that are being made to support drug development work in children, including in fragile newborns, can be extended to the study of other vulnerable populations such as pregnant and lactating women .…”
Section: Next Steps and Remaining Questionsmentioning
confidence: 99%